Inovasi Pelayanan Publik Aplikasi SIMPUS GIZKIA di Kabupaten Boyolali (Studi Kasus di Puskesmas Ngemplak ) - Afaqih Deaz Tratama; Tiyas Nur Haryani (Jurnal Mahasiswa Wacana Publik, 2021)
This study aims to describe the attributes of innovation in the SIMPUS GIZKIA application at the Ngemplak Health Center, Boyolali Regency. This research uses descriptive qualitative research method. Data collection techniques were carried out by interview, observation and documentation and analyzed using an interactive model. The focus of this research is on the theory of innovation attributes by Rogers, namely Relative Advantages, Compatibility, Complexity, Triability and Observability. In the Relative advantages attribute, it is known that the advantages are that the use of paper can be reduced and the effectiveness and efficiency of data management is increasing. The Compatibility attribute shows the SIMPUS GIZKIA application is in accordance with previous innovations, this application is also in accordance with the needs of midwives with this application they feel more practical and faster in managing maternal and infant health data. The SIMPUS GIZKIA application also does not conflict with the values and norms in society so that it can be accepted. Complexity attribute in this application there is no complexity in its use. On the Triability attribute, the SIMPUS GIZKIA application was tested after being socialized to midwives. In the Observability attribute, this application is able to make the process of reporting data from the village midwife to the Boyolali District Health Office easier and faster. The process of monitoring the health conditions of mothers and babies in the village area and the working area of the Puskesmas has become more practical and faster.